ARTICLE SUMMARIES. (Computer (00189162), 2007)
Summaries of articles in the current issue are presented. The software industry in Latin America seeks to improve quality standards through its Competisoft project, which promotes standardization and continual improvement. Another article discusses the importance of embedded systems to a modern economy and the need to make citizens aware of this fact. A third article discusses system-on-chip (SoC) processors. The wide array of digital video products that use SoCs makes impractical a one-size-fits-all solution.